2001
DOI: 10.1111/j.1574-6968.2001.tb10694.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of archaeal 16S rRNA libraries from the rumen suggests the existence of a novel group of archaea not associated with known methanogens

Abstract: Molecular diversity of rumen archaea was analyzed by PCR amplification and sequencing of two 16S rRNA clone libraries prepared from the bovine rumen fluid using two different archaea-specific primer sets. The first library of 19 clones which was generated with primers D30 and D33, produced essentially two groups of sequences, one affiliated with Methanomicrobium mobile (21% of clones) and the other -- with the uncultured archaeal sequences from anaerobic digester, which are distantly associated with Thermoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
105
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(116 citation statements)
references
References 35 publications
10
105
1
Order By: Relevance
“…Many studies have been conducted to investigate the methanogenic diversity in the -E-mail: zhuweiyun@njau.edu.cn rumen. Tajima et al (2001) found that the predominant species were affiliated with Methanomicrobium mobile in the rumen of Holstein dry cows in Japan. From the rumen of Hereford-Cross cattle in Ontario, almost half of the clones of archaea were related to Methanobrevibacter ruminantium (Wright et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Many studies have been conducted to investigate the methanogenic diversity in the -E-mail: zhuweiyun@njau.edu.cn rumen. Tajima et al (2001) found that the predominant species were affiliated with Methanomicrobium mobile in the rumen of Holstein dry cows in Japan. From the rumen of Hereford-Cross cattle in Ontario, almost half of the clones of archaea were related to Methanobrevibacter ruminantium (Wright et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…are members of the order Methanomicrobiales that appear to be abundant in certain rumens (Yanagita et al, 2000;Tajima et al, 2001;Shin et al, 2004;Chaudhary et al, 2012), although the basis of their apparent dominance over Methanobrevibacter spp. in those cases is not known.…”
Section: Overview Of Rumen Ecology/methanogensmentioning
confidence: 99%
“…In foregut fermenters, bacterial cells are degraded later in the acidic stomach, where gastric lysozyme acts as a digestive enzyme (Ruiz et al, 1994) and bacterial biomass is the animal's main source of protein (Stevens and Hume, 1995). The rumen harbors all three domains of life: bacteria (mostly Firmicutes and the PrevotellaBacteroides (Tajima et al, 2001a;Eckburg et al, 2005)); archaea (such as Methanobrevibacter and Thermoplasma (Tajima et al, 2001b)); and eukarya, both protozoa (ciliates and flagellates; (Orpin, 1976;Vogels et al, 1980) and fungi (anaerobic phycomycetes (Mackie, 1997)). …”
Section: Introductionmentioning
confidence: 99%